ANALISIS FINANCIAL DISTRESS DAN BEBERAPA VARIABEL PREDIKTORPADA SEKTOR PERBANKAN DI INDONESIA - Sumani Sumani; Andri Setiawan (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Abstract: The Purpose of this study is (1) to analyze financial distress as predictor variables of financial difficulty levels banking which is listing on the Stock Exchange (BEI), and (2) determine the financial ratios, including CAR, ROE, NPL, NIM, LDR, ROA, BOPO, and the primary reserve as predictor variables of financial distress in banking sector which is listing on the BEI. The population of this study were 38 banks which is listed on the BEI until December 31th, 2014. Number of samples were 30 banks by purposive sampling technique. The analysis tool of study used Logit regression because of dependent variable was dummy variable and the independent variables were a combination of metric and non-metric. The results showed (1) banks were listed on the BEI has good performance (financial difficulties at low levels), the analysis result of financial distress by using multiple predictor variables, such as CAR, ROE, NPL, NIM, LDR, BOPO and reserves' primary GWM has good average value where is level of accuracy (97.2) in classifying the bank's financial difficulties; (2) The hypothesis testing showed a number of variables such as CAR, ROE, NIM, LDR, and BOPO were not significant as a predictor of financial distress in banking where listed on the BEI. However, NPL and reserves' primary GWM were significant variable as predictor of financial distress in banking where listed on the BEI. Keywords: Reserves' primary GWM, Non-Performing Loan, Financial Distress